2020
DOI: 10.1007/978-3-030-45002-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for User Acceptance of Mobile Health Applications for Diabetic Patients: Applying the UTAUT Model

Abstract: The literature illustrates that technology will widen health disparity if its use is restricted to patients who are already motivated and demonstrate good self-management behaviours. Additionally, despite the availability of free mobile health (m-health) applications for diabetes self-management, usage is low. There are also limited studies of m-health acceptance in South Africa. This research is delineated to the Western Cape, South Africa. The populace suffers from increasing numbers of diabetic patients. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…However, researchers have adapted the model outside this context. This has included applying the UTAUT to characterise factors in the literature that enable adoption of EMRs [ 21 ], to deductively analyse qualitative interview data [ 22 , 23 ] and to design semi-structured interview guides based on UTAUT constructs. Refer to Figure 1 to see a process diagram showing how the study data was collected and analysed…”
Section: Methodsmentioning
confidence: 99%
“…However, researchers have adapted the model outside this context. This has included applying the UTAUT to characterise factors in the literature that enable adoption of EMRs [ 21 ], to deductively analyse qualitative interview data [ 22 , 23 ] and to design semi-structured interview guides based on UTAUT constructs. Refer to Figure 1 to see a process diagram showing how the study data was collected and analysed…”
Section: Methodsmentioning
confidence: 99%
“…The UTAUT Model adopted in this study is the acceptance and evaluation tool widely used in the application of science and technology to the users, and the calculation method and evaluation data adopted in this study are in accordance with the standard framework of UTAUT Model [45,46], and there is no difference. The UTAUT Model used in this study is only adjusted according to the elements of the structure, and uses the experimental procedures and methods set by the previous researchers [47,48]. The sample population of the experts and the elderly are required to master the reliability and validity to improve the performance of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that some of the UTAUT variables are losing significance, while others endow the model with greater explanatory power. Among these variables, perceived risk (Al-Saedi et al, 2020 ; Arfi et al, 2021 ) and resistance to use (Dwivedi et al, 2020 ; Petersen et al, 2020 ) are particularly worthy of note. For this reason, to extend the UTAUT and achieve a greater explanatory capacity to the Big Data adoption, we added the variables Resistance to Use (Polites and Karahanna, 2012 ; Lapointe and Rivard, 2017 ) and Perceived Risk (Featherman and Pavlou, 2003 ; Jia et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%